2001
DOI: 10.1177/153857440103500602
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy in Patients with Renal Insufficiency: Should Selection Criteria be Different in Patients with Renal Insufficiency?

Abstract: The objective of this study was to elucidate the relationship between outcomes from carotid endarterectomy (CEA) in patients with and without renal insufficiency. Carotid endarterectomy is one of the most commonly performed vascular procedures. The role of cardiac comorbidity in carotid endarterectomy has been extensively studied. The relationship between renal failure and surgical outcomes has also been studied for both coronary artery bypass grafting and lower extremity occlusive disease. However, the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In 497 patients separated according to the level of creatininemia Ͻ 1.8 mg/dL (n ϭ 448) or Ͼ 1.8 mg/dL (n ϭ 49), Ayerdi et al 14 reported an incidence of MI of 5.4% and 28.6%, an incidence of postoperative stroke of 2.7% and 2.0%, and mortality of 0.9% and 8.2%, respectively, thus confirming the negative impact of RI on the results of carotid surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 497 patients separated according to the level of creatininemia Ͻ 1.8 mg/dL (n ϭ 448) or Ͼ 1.8 mg/dL (n ϭ 49), Ayerdi et al 14 reported an incidence of MI of 5.4% and 28.6%, an incidence of postoperative stroke of 2.7% and 2.0%, and mortality of 0.9% and 8.2%, respectively, thus confirming the negative impact of RI on the results of carotid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] These studies used different definitions of renal insufficiency (RI). Certain authors used plasma levels of creatinine to define groups of patients, 5,7,8,10,14 others considered that creatinine clearance gave a better assessment of renal function, 1 and others associated the two. 9 Furthermore, different levels were used to constitute the groups.…”
mentioning
confidence: 99%
“…There have been several studies which have evaluated the impact of ESRD on patients undergoing CEA; however, the conclusions from these analyses have been varied. [7][8][9] This study found that patients with ESRD were three times more likely to die compared to NF patients as at greater risk for respiratory and septic complications. Okawa et al reported disparate conclusions in a small retrospective chart review.…”
Section: Discussionmentioning
confidence: 68%
“…There have been varied conclusions reported on the risks of CKD in patients undergoing CEA, from no increase in risk to a detrimental increase in complications and death. [7][8][9][10][11][12][13][14][15][16][17] The objective of this analysis was to evaluate the morbidity and mortality of CEA in patients with ESRD and CKD utilizing the Nationwide Inpatient Sample (NIS) database.…”
Section: Introductionmentioning
confidence: 99%
“…This method, however, does not allow for the reliable quantification of calcification and plaque vulnerability. 5,7,13 Degradation of the vessel wall, particularly by matrix metalloproteinases (MMPs), together with an increased inflammatory reaction, are the main reasons for plaque progression toward rupture and consequent neurologic symptoms. [14][15][16] Furthermore, several studies and our own data have already demonstrated increased levels of MMPs in the blood of patients with advanced carotid atherosclerosis.…”
mentioning
confidence: 99%